1999
DOI: 10.1034/j.1399-0012.1999.130606.x
|View full text |Cite
|
Sign up to set email alerts
|

Deciding on cadaveric organ donation in Black African families

Abstract: This study explores factors that have affected the decision of Black African families to donate cadaveric organs. Semi-structured interviews were conducted with ten families living in greater Cape Town, South Africa. Addresses were obtained from records of the transplant co-ordinators at Groote Schuur Hospital. The data were analysed according to broad themes emerging from the interviews. The most important themes were the influence of violent, criminal deaths; the need for a longer period of consultation amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 1 publication
3
19
0
3
Order By: Relevance
“…Although obtaining informed autopsy consent is to elicit the family's (and deceased patient's) religious, cultural and ethical sensitivities and determine what information is significant to decision making (19–22), the study found that family consent was deemed important to appease ancestors so that misfortunes are associated with causes other than the wrath of their ancestors. This finding is similar to other low-income settings that found that the initial decision making for informed consent was vested in the community rather than in the individual (20, 23). …”
Section: Discussionsupporting
confidence: 84%
“…Although obtaining informed autopsy consent is to elicit the family's (and deceased patient's) religious, cultural and ethical sensitivities and determine what information is significant to decision making (19–22), the study found that family consent was deemed important to appease ancestors so that misfortunes are associated with causes other than the wrath of their ancestors. This finding is similar to other low-income settings that found that the initial decision making for informed consent was vested in the community rather than in the individual (20, 23). …”
Section: Discussionsupporting
confidence: 84%
“…This importance of having an intact body is stressed in certain religious groups and is associated with respect for the ancestors and the idea of an after-life [46,48]. Kometsi and Louw [43] further explored the concept of ancestors which is defined as "a belief, that after death, one joins a spiritual world that works in collaboration with and in immediate subordination to God over humankind". Satyapal [77] reiterated that their 'spirits' (amadlozi) should also be at peace.…”
Section: Introductionmentioning
confidence: 99%
“…. for thinking about racial and ethnic minorities as collective social actors -as communities, embedded in fields of power relations' it still retains an essentialist 'understanding of races as discrete categorical groups' (Epstein 2008, 803; for an example in South Africa see Kometsi 1998).…”
Section: E Averamentioning
confidence: 99%